Finnegans wakes : tales of translation - O'Neill, Patrick, 1945- (University of Toronto Press, 2022)
"James Joyce's astonishing final text, Finnegans Wake (1939), is universally acknowledged to be entirely untranslatable. And yet, no fewer than fifteen complete renderings of the 628-page text exist to date, in twelve different languages altogether--and at least ten further complete renderings have been announced as underway for publication in the early 2020s, in nine different languages. Finnegans Wakes delineates, for the first time in any language, the international history of these renderings and discusses the multiple issues faced by translators. The book also comments on partial and fragmentary renderings from some thirty languages altogether, including such perhaps unexpected languages as Galician, Guarani, Chinese, Korean, Turkish, and Irish, not to mention Latin and Ancient Egyptian. Excerpts from individual renderings are analysed in detail, together with brief biographical notes on numerous individual translators. Chronicling renderings spanning multiple decades, Finnegans Wakes illustrates the capacity of Joyce's final text to generate an inexhaustible multiplicity of possible meanings among the ever-increasing number of its impossible translations."--